2012
DOI: 10.1111/iju.12055
|View full text |Cite
|
Sign up to set email alerts
|

Silodosin versus naftopidil in Japanese patients with lower urinary tract symptoms associated with benign prostatic hyperplasia: A randomized multicenter study

Abstract: Abbreviations & Acronyms AR = adrenoceptor BPH = benign prostatic hyperplasia IPSS = International Prostate Symptom Score LUTS = lower urinary tract symptoms Qmax = maximum urinary flow rate QOL = quality of life SAS = statistical analysis system Correspondence: Toshiro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…A clinical study in men with LUTS/BPH showed that silodosin more significantly improved the changes of storage symptom scores than those of naftopidil . In contrast, another clinical study reported that changes from the baseline of storage symptoms in the naftopidil‐treated group tended to be larger than those in the silodosin‐treated group .…”
Section: Discussionmentioning
confidence: 98%
“…A clinical study in men with LUTS/BPH showed that silodosin more significantly improved the changes of storage symptom scores than those of naftopidil . In contrast, another clinical study reported that changes from the baseline of storage symptoms in the naftopidil‐treated group tended to be larger than those in the silodosin‐treated group .…”
Section: Discussionmentioning
confidence: 98%
“…Tamsulosin, naftopidil, silodosin, terazosin, urapidil and prazosin are approved in Japan, and are apparently of comparable efficacy. The former three have shown ample evidence for efficacy . Postural hypotension and asthenia can occur as rarely as a placebo (4–10%).…”
Section: Treatmentmentioning
confidence: 99%
“…Consequently, it still remains largely untested whether the reported efficacy and safety of naftopidil in Japanese and Asian people are generally applicable to non-Asian populations. (4) In the comparative studies with tamsulosin [11][12][13][15][16][17][18]20 , the dose of tamsulosin was lower than the recommended dose in Western countries. This discrepancy makes all comparative studies with tamsulosin inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy makes all comparative studies with tamsulosin inconclusive. (5) Two recent comparative studies report a higher efficacy of silodosin 18,19 , administered as standard, in terms of improvement of both IPSS and QOL score, when compared to naftopidil. Based on these data, it may be postulated that the non-inferiority of naftopidil compared to tamsulosin in the management of LUTS may be due exclusively to the use of a nonstandard dose of tamsulosin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation